CIRCLE EQUATION (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
To make an equilateral inner Pentagon that attempts a circle with radius R and center O in the article, the desired circle radiusiR is calculated by multiplying the coefficient K by the size of one side of the regular pentagonal Watar L distance, that is, the radius value R1 has been determined.